Study on mechanical properties of solidified silt from waste rock powder and stability of subgrade slope - Wang, Lei; Lu, Wei; Cheng, Jinsheng; Li, Jun; Tian, Changjin; Lin, Weinan; Meng, Lingxiao; Zhang, Yiwen (Frontiers in Earth Science, 2025)
Huangfan District silt exhibits discontinuous grading, low structural integrity, and insufficient binder content, failing to meet traffic subgrade specifications. This study employs alkali-activated basalt powder and slag (solid wastes) to form geopolymers for silt stabilization, analyzing stabilized soil subgrade slope stability. Key findings: (1) Alkali-activated basalt-slag synergy enhances mutual hydration, producing N-A-S-H and C-A-S-H cementitious gels. (2) Geopolymer content positively correlates with compressive strength, peaking at 20% dosage (2.74 MPa) - a 30.4-fold increase over natural silt, exceeding specification requirements by 10.96-fold. (3) Shear strength increases with vertical pressure and additives (NaOH, Na2SiO3, slag), showing significantly improved internal friction angle and cohesion versus natural silt. (4) With the increase of the content of geopolymer in solidified soil, the maximum vertical displacement of the roadbed surface and the displacement of the slope gradually decrease. The stress is mainly concentrated in the tire grounding area and gradually decays along the depth direction. The vertical stress values at other positions of the road slope are maintained at a low level.